2017
DOI: 10.18203/2349-3291.ijcp20164413
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and etiological spectrum of fever of unknown origin in children aged 2 months to 12 years

Abstract: Background: Fever of unknown origin is one of the leading etiologies for morbidity and mortality among children worldwide and their spectrum keeps changing constantly from time to time. The objective of this study was to study the clinical profile and etiological spectrum of fever beyond 2 weeks duration in children aged 2 months to 12 years admitted in a tertiary care hospital. Methods: A prospective observational study, done in tertiary care centre over six month period (May 2016 to October 2016). Children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Infections are the main cause for FUO constituting 60-70% 8 . In our study they accounted for 70.8% similar to studies by Landge A A et al (79%), Santosh G et al (69.1%) and Joshi N (69%) 9,10,11 . Table 2 shows the percentages of various causes in different studies.…”
Section: Discussionsupporting
confidence: 89%
“…Infections are the main cause for FUO constituting 60-70% 8 . In our study they accounted for 70.8% similar to studies by Landge A A et al (79%), Santosh G et al (69.1%) and Joshi N (69%) 9,10,11 . Table 2 shows the percentages of various causes in different studies.…”
Section: Discussionsupporting
confidence: 89%
“…For example, in a retrospective study conducted by Sumathisri et al infectious disease was responsible for 90.6%, similarly Nalli et al 1 got an incidence of 38% as infectious cause of PUO, Govindarajulu et al found incidence of 69.1%. 1,11,14 Among infectious causes, the major proportion (17.5%) was respiratory tract infection, followed by scrub typhus (13.5%), urinary tract infections (10%). Typhoid and TB contributed 8% each to PUO in the study population.…”
Section: Resultsmentioning
confidence: 99%
“…18 Other studies as done by Nalli et al, Govindarajulu et al also had findings similar to our study and in both studies, malignancy was the second most common cause of PUO with a higher proportion than collagen vascular disorders. 1,14 Among participants with malignancy, the most common diagnosis was acute lymphoblastic leukemia (7%) followed by acute myeloid leukemia (2.5%). Nalli et al also in his prospective, observational study discovered the commonest malignancy causing PUO in pediatric patients being acute lymphoblastic leukemia.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Another study among paediatric population found enteric fever and acute lymphoblastic leukemia as the most frequent causes. [16] As obtained by D.Prabahkumar et al, there has been a fall in the incidence of infections ranging from 16%-57%,in parallel to increase in diagnosis of inflammatory disorders attributed mainly due to increased awareness and advances in diagnostic facilities. [17] It is to be noted that even after the introduction of ongoing Revised National Tuberculosis Control Program (RNTCP) from 1997, the scourge of Tuberculosis still plagues our rural population.…”
Section: Discussionmentioning
confidence: 99%